Exploring the effect of changes to service provision on the use of unscheduled care in England: population surveys - Munro James; Knowles Emma; O'Cathain Alicia; Nicholl Jon (BMC, 2007)
Abstract Background Unscheduled care is defined here as when someone seeks treatment or advice for a health problem without arranging to do so more than a day in advance. Recent health policy initiatives in England have focused on introducing new services such as NHS Direct and walk in centres into the unscheduled care system. This study used population surveys to explore the effect of these new services on the use of traditional providers of unscheduled care, and to improve understanding of help seeking behaviour within the system of unscheduled care. Methods Cross-sectional population postal surveys were undertaken annually over the five year period 1998 to 2002 in two geographical areas in England. Each year questionnaires were sent to 5000 members of the general population in each area. Results The response rate was 69% (33,602/48,883). Over the five year period 16% (5223/33602) 95%CI (15.9 to 16.1) of respondents had an unscheduled episode in the previous four weeks and this remained stable over time (p = 0.170). There was an increased use of telephone help lines over the five years, reflecting the change in service provision (p = 0.008). However, there was no change in use of traditional services over this time period. Respondents were most likely to seek help from general practitioners (GPs), family and friends, and pharmacists, used by 9.0%, 7.2% and 6.3% respectively of the 5815 respondents in 2002. Most episodes involved contact with a single service only: 7.0% (2363/33,602) of the population had one contact and 2% (662/33602) had three or more contacts per episode. GPs were the most frequent point of first contact with services. Conclusion Introducing new services to the provision of unscheduled care did not affect the use of traditional services. A large majority of the population continued to turn to their GP for unscheduled health care.